Wizjoner przyszłości – Norman Bel Geddes. Design jako sposób na budowanie lepszego jutra - Kozina, Irma (Załącznik Kulturoznawczy, 2019)
The American industrial designer Norman Bel Geddes is known for developing innovative concepts about theatre and movie sets, as well as designing cars based on streamlining. Moreover, he also belonged to the early-twentieth-century avant-garde pioneers who tried to combine the utopian vision of a better future with new perspectives occasioned by the advent of human flight. The 1920s and 1930s are considered the golden age of American aviation. They are believed to have ushered in new spacial dynamics that were supposed to result in the introduction of the city of tomorrow. The present article examines the relationship between the enthusiasm for aerial vision expressed in the Futurama project prepared by Bel Geddes for the 1939 New York World’s Fair and the utopian concepts of a better future, traditionally created as a certain kind of answer to patriotic jeremiads containing ideas of social optimism, essential for achieving a promise of a better future.